Sexual function outcomes in prostate and cervical cancer patients treated with radiotherapy in sub-Saharan Africa: A cross-sectional study. - Joseph Daniels; Kofi Adesi Kyei; Prince Dela Frimpong-Boateng; Andrew Yaw Nyantakyi (PLoS ONE)
Radiotherapy is indispensable for the successful treatment of many pelvic malignancies, but it is often associated with significant adverse effects on sexual function, including vaginal stenosis, decreased lubrication, erectile dysfunction, and loss of libido. Sexuality and sexual function are important aspects of quality of life for cancer survivors, yet sexual dysfunction remains an underreported complication among patients, particularly those treated for prostate and cervical cancers in limited-resource settings. This quantitative cross-sectional study aimed to evaluate sexual function outcomes among 144 prostate and 160 cervical cancer patients treated with pelvic radiotherapy at a major cancer treatment centre in sub-Saharan Africa. Data were collected using questionnaires based on the Female Sexual Function Index and the International Index of Erectile Function. Data were coded, cleaned, and analyzed using STATA statistical software package (version 17). The mean age of the patients with cervical cancer was 53.5 years (SD 9.6) ranging from 37 to 69 years whereas the mean age of patients with prostate cancer was 67.1 years (SD 7.7) ranging from 56 to 79 years. Among female participants, 79.9%, had moderate to severe sexual dissatisfaction, 94.4% had poor or no satisfactory orgasm whereas 97.2% had difficulty with lubrication. Only 5.6%, 5.6%, 2.8%, and 20.1% of the female participants achieved sexual desire, orgasm, lubrication, and overall satisfaction respectively. In all, 94.4% of the female participants had a total FSFI score less than 26 whereas 5.6% had a score greater than 26. Most patients did not indulge in sexual activity. There was a high prevalence of sexual dysfunction across multiple domains, with cervical cancer patients experiencing diminished desire, poor arousal, lubrication difficulties, and impaired orgasmic function, leading to low relationship satisfaction and avoidance of sexual activity. Similarly, prostate cancer patients demonstrated severe erectile dysfunction, low sexual desire, and dissatisfaction with intercourse and overall sexual experience.